2016
DOI: 10.1369/0022155416675153
|View full text |Cite
|
Sign up to set email alerts
|

Triple Staining Including FOXA2 Identifies Stem Cell Lineages Undergoing Hepatic and Biliary Differentiation in Cirrhotic Human Liver

Abstract: SummaryRecent investigations have reported many markers associated with human liver stem/progenitor cells, "oval cells," and identified "niches" in diseased livers where stem cells occur. However, there has remained a need to identify entire lineages of stem cells as they differentiate into bile ducts or hepatocytes. We have used combined immunohistochemical staining for a marker of hepatic commitment and specification (FOXA2 [Forkhead box A2]), hepatocyte maturation (Albumin and HepPar1), and features of bile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…However, in liver samples from patients with Child-Pugh A, B, and C, a substantial number of hepatocytes became positive for FOXA2, supporting that reprogramming of biliary endothelial cells to hepatocytes or vice versa is also operative in human liver. (20,32) Our findings indicate that failure of the hepatic transcription system appears to be a pathologic finding in liver disease progression. These findings suggest that any correlation between chronic liver failure in cirrhosis in humans and HNF4a-dependent hepatic functions is not regulated at the level of HNF4a transcription but rather at the level of protein expression and/or nuclear localization.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…However, in liver samples from patients with Child-Pugh A, B, and C, a substantial number of hepatocytes became positive for FOXA2, supporting that reprogramming of biliary endothelial cells to hepatocytes or vice versa is also operative in human liver. (20,32) Our findings indicate that failure of the hepatic transcription system appears to be a pathologic finding in liver disease progression. These findings suggest that any correlation between chronic liver failure in cirrhosis in humans and HNF4a-dependent hepatic functions is not regulated at the level of HNF4a transcription but rather at the level of protein expression and/or nuclear localization.…”
Section: Discussionmentioning
confidence: 66%
“…For instance, protein expression of FOXA2 in biliary endothelial cells remained consistent in all liver samples examined in this study. However, in liver samples from patients with Child‐Pugh A, B, and C, a substantial number of hepatocytes became positive for FOXA2, supporting that reprogramming of biliary endothelial cells to hepatocytes or vice versa is also operative in human liver …”
Section: Discussionmentioning
confidence: 99%
“…Its members play important roles in regulating cellular proliferation [50] and differentiation [51][52][53]. As FOXA2 is expressed early during fetal liver development and not expressed in mature hepatocytes or bile duct cells, it might represent an excellent marker of early stage hepatic stem/progenitor cells, HPC [54]. Nobili et al [55] assessed the role of HPC in pediatric NAFLD comparing histologic specimens isolated from normal controls, fatty livers and NASH.…”
Section: Discussionmentioning
confidence: 99%
“…Zhou et al revealed by NCAM, CK19, and HepPar1 staining that DR embedded in cirrhotic tissues had a distinct hepatocyte and biliary tract bipolar structure 41 . Charles et al used a multi-marker approach to detect FoxA2, HepPar1, albumin, CK19, and miRNA expression to track differentiation in the stem cell lineage during end-stage cirrhosis, indicating a bifurcation direction of HPCs differentiation 42 .…”
Section: Activation and Differentiation Of Adult Hpcsmentioning
confidence: 99%